(untitled) (Journal of Mathematical Study, 2024)
In this paper, we study the group extension of a Tambara-Yamagami category which has Frobenius-Perron dimension 2pq, where p,q are prime numbers. We prove that there are two possible category types when p e q, and five possible category types when p=q.